Changes in plasma homocysteine levels of rats with experimentally induced hypothyroidism and hyperthyroidism - Özkan, Y; Dönder, E; Güney, H; Baydas, G (Maghira & Maas Publications, 2005)
INTRODUCTION: It is claimed in a limited number of studies carried out on human beings that plasma homocysteine levels increased in hypothyroid patients and decreased in hyperthyroid patients. OBJECTIVE: The aim of this study is to determine total plasma homocysteine, thyroid function tests, vitamin B12, folic acid and lipid levels and to explore the relations among them in rat models with induced hypothyroidism and hyperthyroidism with a view to investigating whether hypothyroid and hyperthyroid rat models could represent human hypothyroidism and hyperthyroidism models. MATERIAL AND METHOD: The study included 30 male Wistar Albino species rats with a mean weight of 200-250 g. Rats were randomly divided into 3 groups as 1) hypothyroid group, 2) hyperthyroid group and 3) control group. Hypothyroidism was induced by adding 10 mg/kg/day propylthiouracil to rats' drinking water for 30 days. In order to induce hyperthyroidism, rats were administered 10 mu g/100 g L-thyroxin ampule via intraperitoneal route for 10 days. RESULTS: We found that total plasma homocysteine level of the hypothyroid group was significantly lower than those of the control group (p < 0.05) and the hyperthyroid group (p < 0.001). Total plasma homocysteine level of the hypothyroid group was found insignificantly higher than that of the control group (p > 0.05) and significantly higher than that of the hyperthyroid group (p < 0.001). We established a significant and positive correlation between total plasma homocysteine level and thyroid hormone levels. We did not identify a significant relation between total plasma homocysteine level and serum folic acid and serum vitamin B12 levels. CONCLUSION: Our findings are different from the findings reported in human hypothyroidism and hyperthyroidism studies. We believe that hypothyroid and hyperthyroid rat models cannot represent human hypothyroidism and hyperthyroidism models.
Keywords: experimental hypothyroidism; experimental hyperthyroidism; homocysteine; rat